Balaam and Motivation of Contemporary Church Leaders - Yonatan Alex Arifianto; Daniel Supriyadi; Kharisda Mueleni Waruwu; Johanes Paryono (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
The life of a pagan prophet from Moab named Balaam is an exciting lesson about leadership to study. This prophet represents a materialistic lifestyle, disobedience to God, and disobedience of service in the name of God. His ministry was in a historical setting where Israel also experienced severe moral decadence as God's people. This article will reveal and analyze how Balaam's role as a reflection of contemporary leadership in the church is strongly influenced by the concepts of materialism, hedonic lifestyle, and highly pay-oriented leadership. Through a qualitative descriptive approach, this study uses some works of literature as the main study. Through Balaam's life, contemporary church leaders could learn about the importance of integrity and genuine ministry motivation. The exemplary aspect is an essential factor that leaders must own. We also found that leaders need to serve with a servant spirit, as Jesus had shown. Only in this way can a leader have an honorable and consistent life in the values of the truth of God's word.